Challenges facing sub‐Saharan small‐scale farmers in accessing farming information through mobile phones: A systematic literature review. Issue 4 (21st June 2018) - Misaki, Ezra; Apiola, Mikko; Gaiani, Silvia; Tedre, Matti
Abstract: The use of mobile phone technology has increasingly been advocated to assist small‐scale farmers. Accordingly, numerous studies have been conducted on the impact, effectiveness, user's attitude, assessment, empowerment, and the potential use of mobile phone technology in agriculture. This study explores the challenges that small‐scale farmers in sub‐Saharan Africa face when using a mobile phone technology in crop farming projects and proposes areas for future improvement. The study used a systematic literature search conducted by authors at 3 levels, in which 134 studies initially identified were then narrowed to 11. These 11 studies generated 7 projects that use specialized applications in a farming value chain. The findings from the study indicate some of the challenges faced by small‐scale farmers, including the lack of their involvement in the initial phase of the invention process. Other obstacles include low trust and transparency, inappropriate use of foreign language (English) in a local cultural context, bureaucracy, and theft of mobile phones. On the basis of these results, the authors conclude that there are generalized factors for understanding deficiencies experienced by small‐scale farmers, which ought to be understood by all crop farming stakeholders. These factors can be used by software engineers to design future technologies beneficial to small‐scale farmers.